VD_FINDINFO Jug / 2012 / 38 vom 5. Oktober 2011 - VD Tribunal cantonal (2011)
ASSISTANCE JUDICIAIRE, AVOCAT D'OFFICE, PLAIGNANT, DÉPENS, MEILLEURE FORTUNE | 135 al. 4 let. a CPP (CH), 135 al. 4 let. b CPP (CH), 138 CPP (CH), 426 al. 4 CPP (CH), 433 al. 1 CPP(CH)